Narratives of bullying and emersion of self-compassion expressions in adolescents - Gonçalves,Francisca Valda (2021)
Abstract This study aimed to investigate the narratives of bullying and the expression of self-compassion in statements written by adolescents as a possible coping strategy. Participated 162 adolescents from a state in northern Brazil. The data collected in written testimonials were categorized based on Bardin’s Content Analysis. The instructions provided for preparing the testimonies supported the structuring of four categories: 1) bullying experience; 2) reasons for bullying; 3) consequences of bullying; 4) coping strategies and self-compassion expressions. The results suggest 63.7% of adolescents witnessed bullying behaviors. Physical characteristics were the main motivation reported toward bullying. Negative feelings and psychosomatic symptoms were the main consequences reported. The adolescents reported forms of self-compassion as a coping resource before receiving psychoeducation about the concept. The implications of these findings and the use of psychoeducational interventions on bullying and self-compassion are discussed.